2004
DOI: 10.1128/iai.72.6.3218-3227.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of EspF from Enteropathogenic and Enterohemorrhagic Escherichia coli in Alteration of Epithelial Barrier Function

Abstract: Enteropathogenic Escherichia coli (EPEC) and enterohemorrhagic E. coli (EHEC) are related intestinal pathogens that harbor highly similar pathogenicity islands known as the locus of enterocyte effacement (LEE). Despite their genetic similarity, these two pathogens disrupt epithelial tight junction barrier function with distinct kinetics. EHEC-induced reduction in transepithelial electrical resistance (TER), a measure of barrier function disruption, is significantly slower and more modest in comparison to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 42 publications
1
89
1
3
Order By: Relevance
“…Unfortunately, we did not screen for Abcf2 and N-WASP, but screened for the same ATP-binding cassette family of ABCA3. First, the espF gene sequences of EPEC and EHEC were 87% identical, although they had high similarity, their pathogenicity appeared to be different, for example, in reducing the function of epithelial resistance (TER) [69]. Second, the N-terminal of EspF protein in EPEC and EHEC includes the bacterial secretion signal site and the two organellar targeting domains.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we did not screen for Abcf2 and N-WASP, but screened for the same ATP-binding cassette family of ABCA3. First, the espF gene sequences of EPEC and EHEC were 87% identical, although they had high similarity, their pathogenicity appeared to be different, for example, in reducing the function of epithelial resistance (TER) [69]. Second, the N-terminal of EspF protein in EPEC and EHEC includes the bacterial secretion signal site and the two organellar targeting domains.…”
Section: Discussionmentioning
confidence: 99%
“…Using tandem MS, we observed many of the established proteins that have been shown to be secreted by EHEC O157. These included the Esp family of translocon proteins (EspA, B, D and F) (Abe et al, 1998;Viswanathan et al, 2004), the translocated intimin receptor, Tir (DeVinney et al, 1999), the mitochondrion-associated protein, Map (Kenny & Jepson, 2000), secreted proteases EspP (Brunder et al, 1997) and StcE (Lathem et al, 2002) (both encoded on pO157), and enterohaemolysin (Schmidt et al, 1995) (also on pO157). Using this wild-type strain, only NleA of the Nle A subpopulation of bacteria expressed nleA : : gfp, and only these bacteria were analysed for fluorescence output.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it could be argued that the observed inhibition of apical Cl -/OH -exchange activity in response to EPEC infection could also be contributed by the DIDS-sensitive basolateral anion transporters. In this regard, our previous studies have suggested that infection of human intestinal epithelial cells with EPEC does not cause any transepithelial electrical resistance (TER) changes until 3 hours (5,39). Thus, in the absence of permeability changes, apical 36 Cl -uptake would be primarily facilitated by DRA and PAT-1.…”
Section: Figurementioning
confidence: 99%